Supported nickel nitride catalysts for the gas-phase hydrogenation of furfural - Jiménez-Gómez, Carmen Pilar; Cecilia-Buenestado, Juan Antonio; Defilippi, Chiara; Maireles-Torres, Pedro Jesús; Giordano, Cristina (My University, 2019)
A series of catalysts with different nickel loading (2.5-30 wt%) has been prepared by UGR. The preparation of Ni3N phase was ascertained via Powder X-rays diffraction together with cubic nickel . The elemental chemical analysis and XPS data confirm the presence of the nitride phase. Their catalytic performance points out that catalysts with loading of 5-10 wt% Ni exhibit a higher stability, maintaining furfural conversion values higher than 75% after 5 h of time-on-stream at 170ºC, and the main products detected were furfuryl alcohol (hydrogenation) and furan (decarbonylation). This would indicate that two types of active sites are present on the catalyst surface. It is noteworthy the high catalytic activity of this family of catalyst, since they exhibit a better performance than Cu-ZnO catalysts, but using a lower reaction temperature and H2/furfural molar ratio, as well as a higher furfural concentration and WHSV values. The experimental conditions have been optimized in order to achieve the maximum yield in the target product, but preserving a high activity and stability. The fresh and spent catalysts have been characterized in order to elucidate structure-activity-stability relationships.
Keywords: Nitruros; Hidrogenación; Biomasa -- Conversión; Biorefinery; nickel nitride; furfural hydrogenation